EFISIENSI PENJUALAN TEMBAKAU VERGINIA BERDASARKAN BENTUK DAUN BASAH DAN DAUN KERING DI KECAMATAN SAKRA BARAT KABUPATEN LOMBOK TIMUR - Jamaluddin Jamaluddin; Mimi Cahayani (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
To be able to determine the type of tobacco that provides maximum profit for farmers in Lita from the types of tobacco leaf forms that are sold, it is necessary to conduct a study entitled "Economic Efficiency of Virginia Tobacco Farming Based on the Forms of Selling Wet Leaves and Dry Leaves in Sakra Barat District, East Lombok Regency" . Efficiency measurement using Revenue Cost Ratio (R / C). The unit of analysis in this research is farmers who do Virginia tobacco farming in the form of selling wet and dry leaves. Of the 16 Villages in West Sakra Subdistrict, four villages were selected by purposive sampling with the consideration that the four villages had the highest number of Virginia tobacco farmers. The four villages are Rensing Village, Jero gunung Village, Pematung Village, Rensing Raya Village. Determination of respondents is done by Quota Sampling, namely sampling based on a certain amount / quota. Based on the results of the analysis, the average income of wet leaf farmers was IDR 7,670,120 / LL or IDR. 065,013 / Ha and the average income of dry leaf farmers was IDR 60,832,656 / LLG or IDR 40,555,104 / Ha. The average R / C value for the sale of wet leaves is 2.4 and the R / C value for dry leaves is 3.4, it means that the sale of wet leaves and dry leaves is equally feasible because they have a higher R / C value> 1. compared to wet leaf sales.